A review on the effects of vitamin D attenuating ischemia reperfusion injuries. Issue 1 (31st December 2022) - Chen, Chaoran; Wan, Xiao; Shang, Jia; Zhang, Wunong; Xie, Zhenxing
ABSTRACT: Ischemia reperfusion (I/R) injuries occurred in many pathological and surgical processes (e.g. thrombolytic therapy, organ transplantation, aortic cross-clamping, coronary angioplasty and cardiopulmonary bypass) and harmed multiple organs and tissues. Vitamin D is a well-known sterol hormone and a nutritional ingredient able to promote the deposit of calcium and regulate phosphorus metabolism in the body. In addition, vitamin D has therapeutic effects on some diseases (e.g. cardiovascular disease, diabetes, cancer, neurological diseases, multiple sclerosis and inflammation). Studies showed that vitamin D3 was closely related with I/R injury occurrences in heart, brain, spine, liver, kidney, and ovary. The literature searching was conducted in PubMed, Embase, Cochrane Library, Web of Science, and SCOPUS from inception to 20 September 2021. Data showed that supplements with vitamin D3 can remarkably attenuate I/R injuries. This paper reviewed recent progresses of vitamin D3 preventing I/R injuries in clinical investigations and animal tests to enlighten future studies.